'Metall auf Metall' – the German Federal Constitutional Court discusses the permissibility of sampling music tracks: Bunderverfassungsgericht BVerfG 1 BvR 1585/13 – 'Metall auf Metall'. Issue 1 (April 2017) - Mimler, Marc D
Abstract : The German Federal Constitutional Court has delivered an important decision with regards to the permissibility of sampling which is widely used in hip hop and electronic music. With this decision, the Court ended a dispute that has been ongoing for almost twenty years. Furthermore, the Court has applied a fundamental rights discourse between the countervailing rights of the original authors and those of the new works using samples from the original works. The preceding courts found that sampling would constitute an infringement of the phonogram producer rights (Section 85 of the German Author's Rights Act) where the samples could have been created independently. The German Constitutional Court, however, disagreed: by holding that sampling was a form of art protected by the fundamental right of artistic freedom and may outweigh the exploitation interest of the phonogram producer, which would only be impaired to a minimal extent by sampling.